2019
DOI: 10.22319/rmcp.v10i1.4327
|View full text |Cite
|
Sign up to set email alerts
|

Mean lethal dose (LD50) and growth reduction (GR50) due to gamma radiation in Wilman lovegrass (Eragrostis superba)

Abstract: La radiación gamma puede ser utilizada como agente mutagénico para inducir variabilidad genética en especies vegetales. No obstante, antes de comenzar un programa de mejoramiento mediante mutagénesis, es necesario establecer la dosis de irradiación adecuada. El objetivo fue determinar la dosis letal media (DL50) y de reducción media del crecimiento (RC50) en pasto garrapata (Eragrostis superba Peyr.). Para ello, se irradió semilla con dosis de 0 (tratamiento testigo), 100, 200, 300, 450, 600, 900, 1400, 2000 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…e ., the higher the doses, the greater the mortality. Therefore, the undesirable mutations obtained remain a way away from the expected conclusion [ 33 ]. Moreover, it is already well established in accordance with the norms of IAEA that gamma irradiation up to the dosage of 10 kGy had no deleterious effect on human health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e ., the higher the doses, the greater the mortality. Therefore, the undesirable mutations obtained remain a way away from the expected conclusion [ 33 ]. Moreover, it is already well established in accordance with the norms of IAEA that gamma irradiation up to the dosage of 10 kGy had no deleterious effect on human health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These GR 50 and LD 50 values are crucial because they result in a greater likelihood of acquiring desirable mutants [22]. According to A ´lvarez-Holguı ´n, et al [33], lower doses of gamma irradiation result in minor alterations to the genome, but higher doses result in undesired or deadly mutations, i.e., the higher the doses, the greater the mortality. Therefore, the undesirable mutations obtained remain a way away from the expected conclusion PLOS ONE [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient induced mutagenesis by gamma radiation requires determination of the optimal radiation dose; that is, the dose that reduces 50% of the population (median lethal dose, LD50) [8]. The LD50 of Karmindo 2 and accessions M03 were different, as well as the LD50 of the Kemiri Sunan 2 variety reported by [7].…”
Section: Ld50 Determinationmentioning
confidence: 99%
“…Meanwhile, [7] has reported that the LD50 of Kemiri Sunan 2 is 93.86 Gray, approaching the LD50 of M03. According to [8] LD50 is influenced by the type of tissue (seed, callus or meristem), the stage of development and the water content in the tissue. M03 is an accession from Majalengka Regency, West Java, as well as the superior variety Kemiri Sunan 2.…”
Section: Ld50 Determinationmentioning
confidence: 99%